GREBEG MAULUD DALAM REPRESENTASI BUSANA DAN MOTIF BATIK DI KERATON YOGYAKARTA - Renta Vulkanita Hasan (Institut Seni Indonesia Yogyakarta, 2012)
Culture growing in Indonesia and overseas intrinsically dynamic. Nature of culture as a result ofhuman creativity is always moving and displacement. When his journey to the vibrant place anyway,culture is likely to mix with the native culture which then grow and develop into a new culture.Culture is a strong factor that affects the mindset. Over time, society has a way of looking at theworld deal, behave, and interact with each other. In other words, they have their own color andpattern of the deal while making rules in social life. Yogyakarta in Java, which is known as one of thecultural centers of Java development, especially ritual Grebeg Maulud. Ritual Grebeg Maulud overtime reflecting the constantly changing movement of social change, culture, politics, economics andsociety in his day. Ritual is a means of connecting Grebeg Maulud transcendental between man andGod (Manunggaling Kawula-Gusti) and guidance from the teachings of the holy book (Islam). But thistime Grebeg Maulud also has another function, namely as a spectacle. This suggests a cultural shiftfrom the sacred to the profane. Batik as a dress code in the Carnival celebrations Grebeg Maulud isone reflection of the existence of culture in Yogyakarta Palace. The use of batik in a ritual processionGrebeg Maulud is a tradition that continues to this day. Batik palace is considered one of the symbolsof the existence of power relations by creating a specific motive for a particular class. Dynamism ofculture led to the use of batik is not only a marker of power relations, but also as an exciting treat forthe fashion show at the Carnival lasts Grebeg Maulud. Keyword: Grebeg, Maulud, representations, clothing, batik, palace, Yogyakarta